1995
DOI: 10.1111/j.1432-1033.1995.714_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated α2‐Macroglobulin Promotes Mitogenesis in Rat Vascular Smooth Muscle Cells by a Mechanism that is Independent of Growth‐Factor‐Carrier Activity

Abstract: Vascular smooth muscle cell (vSMC) proliferation is important in atherosclerosis. We previously demonstrated that methylamine-activated a,-macroglobulin (aLM) and transforming growth factor P1 this study was to determine whether the synergy is due to the ability of cx,M-methylamine (rx,M-MeNHL) to bind TGF-Pl and target the growth factor to vSMCs that express the u2M receptor. Rcceptor-recognized rx, M derivatives without TGF-B1 -binding activity, including ternary a,M-trypsin, an 1 X-kDa proteolytic fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…1B). ␣ 2 M* binds to growth factors and cytokines, but RBF and K1370A lack the growth factor binding domain (44). Thus, these studies demonstrate that the observed effects are related directly to ␣ 2 M* cellular binding.…”
Section: Western Blotting Of C-fos C-myc Creb and Nfb Proteins Inmentioning
confidence: 58%
“…1B). ␣ 2 M* binds to growth factors and cytokines, but RBF and K1370A lack the growth factor binding domain (44). Thus, these studies demonstrate that the observed effects are related directly to ␣ 2 M* cellular binding.…”
Section: Western Blotting Of C-fos C-myc Creb and Nfb Proteins Inmentioning
confidence: 58%
“…Glutathione-Stransferase receptor-associated protein (GST-RAP) was expressed in bacteria and purified as previously described. 28 TaqMan quantitative polymerase chain reaction (qPCR) primers, probes, and reagents were purchased from Applied Biosystems (Foster City, CA). Smart-pool siRNA targeting mouse LRP-1 and nontargeting pooled control (NTC) siRNA were from Dharmacon RNA Technologies (Lafayette, CO).…”
Section: Reagents and Proteinsmentioning
confidence: 99%
“…The 18-kDa receptor-binding domain (RBD) of ␣ 2 M was generated by treating ␣ 2 M-MA with papain and purified by chromatography, as previously described (4). Receptor-associated protein was expressed as a GST fusion protein (GST-RAP) in bacteria and purified as previously described (37). GST-RAP binds to LRP-1 and blocks the binding of all other LRP-1 ligands (38).…”
Section: Methodsmentioning
confidence: 99%